2009
DOI: 10.1002/ijc.24360
|View full text |Cite
|
Sign up to set email alerts
|

RNAi targeting urokinase‐type plasminogen activator receptor inhibits metastasis and progression of oral squamous cell carcinoma in vivo

Abstract: It has been admitted that urokinase-type plasminogen activator receptor (u-PAR) is overexpressed in many human malignant tumors including oral squamous cell carcinoma (OSCC) and plays an important role in a variety of cancer key cellular events as a versatile signaling orchestrator. In our study, a retroviral vector expressing u-PAR-specific siRNA was injected into OSCC xenografts of nude mice to observe its inhibitory effects on OSCC. Our data demonstrate that siRNA targeting u-PAR markedly suppressed tumor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…This may explain why knockdown of HIF-2α had no effect on cell proliferation at either 5% O 2 or 1% O 2 , whereas knockdown of HIF-1α significantly inhibited the cell proliferation at 1% O 2 . uPAR, a serine proteinase receptor, activates plasminogen and matrix metalloproteinase, and finally facilitates matrix remodeling and cell migration (24). We observed that the hypoxic induction of uPAR was regulated by HIF-1α, but not HIF-2α, in OSCC cells, indicating a prometastatic role of HIF-1α in OSCC.…”
Section: Discussionmentioning
confidence: 73%
“…This may explain why knockdown of HIF-2α had no effect on cell proliferation at either 5% O 2 or 1% O 2 , whereas knockdown of HIF-1α significantly inhibited the cell proliferation at 1% O 2 . uPAR, a serine proteinase receptor, activates plasminogen and matrix metalloproteinase, and finally facilitates matrix remodeling and cell migration (24). We observed that the hypoxic induction of uPAR was regulated by HIF-1α, but not HIF-2α, in OSCC cells, indicating a prometastatic role of HIF-1α in OSCC.…”
Section: Discussionmentioning
confidence: 73%
“…92,93 Recent evidence suggests that the RNAi-mediated downregulation of HIF-1a affects vascular endothelial GF expression as well as tumor cell proliferation, angiogenesis, apoptosis, and xenograft growth of OSCC. 68 Similarly, indirect targeting of CK2 by RNAi in HNSCC modulates the DNA-binding activity of NF-kB and p53/ p63, 13 which subsequently induces cell death.…”
Section: Rna Interferencementioning
confidence: 99%
“…RNAi targeting urokinase-type plasminogen activator receptor (u-PAR) induced apoptosis as well as oral cancer invasion and metastasis [55]. Stable transfection of intracellular fragment of Notch induced G0-G1 cell cycle arrest and apoptosis in human tongue cancer cell line (Tca8113), accompanied by down-regulation of Wnt-b-catenin, increase of p21 and p53 expression, and decrease in Skp2 (S-phase kinase-associated protein 2) and Bcl-2 (B-cell lymphocytic-leukaemia protooncogene 2) expression [56].…”
Section: Gene Manipulationsmentioning
confidence: 99%